2020
DOI: 10.1038/s41598-020-59374-9
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for after-effects of noisy galvanic vestibular stimulation on motion perception

Abstract: Noisy galvanic vestibular stimulation (nGVS) delivered at imperceptible intensities can improve vestibular function in health and disease. Here we evaluated whether nGVS effects on vestibular function are only present during active stimulation or may exhibit relevant post-stimulation aftereffects. Initially, nGVS amplitudes that optimally improve posture were determined in 13 healthy subjects. Subsequently, effects of optimal nGVS amplitudes on vestibular roll-tilt direction recognition thresholds (DRT) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 39 publications
(56 reference statements)
4
19
0
Order By: Relevance
“…In agreement with the aforementioned theoretical framework of SR the authors observed a minimum of the threshold at an intermediate nGVS intensity of about 200 to 500 μA peak amplitude. These observations were later confirmed and extended in subsequent studies 19 21 .…”
Section: Introductionsupporting
confidence: 69%
“…In agreement with the aforementioned theoretical framework of SR the authors observed a minimum of the threshold at an intermediate nGVS intensity of about 200 to 500 μA peak amplitude. These observations were later confirmed and extended in subsequent studies 19 21 .…”
Section: Introductionsupporting
confidence: 69%
“…These improvements were further enhanced by a subsequent 30-minute exposure, which also sustained the beneficial effects. However, this sustained effect has not been replicated consistently in other studies; Inukai et al [ 22 ] found a poststimulation effect in contrast to Nooristani et al [ 23 ] and Keywan et al [ 24 ] who did not. A secondary analysis by Fujimoto et al [ 21 ] discovered that noisy galvanic vestibular stimulation resulted in significantly greater improvements in participants who were more unsteady on initial assessment [ 25 ].…”
Section: Introductionmentioning
confidence: 82%
“…Poststimulation behavior effects of GVS are largely unknown (13). Studies that examined GVS aftereffects stimulated participants for more than 30 min, and the results are conflicting (74)(75)(76)(77). The issue of whether stimulation effects last after the cease of stimulation is not only limited to GVS but is one of the main controversial topics for transcranial electrical stimulation (78).…”
Section: Discussionmentioning
confidence: 99%